Analisis Sifat Mekanik Handle Rem Sepeda Motor Berbahan Aluminium A1100 dengan Penambahan Unsur Magnesium - Yasvita, Septania Dwi; Rasid, Muhammad; Arnoldi, Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
Casting is the process of melting materials by heating them using a melting pot. The resulting liquid is then poured into a mold to form an object or product. The aim of this research was to test the mechanical properties of A1100 aluminum alloy with the addition of 3%, 4% and 5% magnesium (Mg), and to see its effect on the Impact strength and hardness values. Impact test results show that the addition of 3%, 4% and 5% magnesium increases the Impact value, with 5% magnesium alloy having the highest Impact value of 1.14 J/cm². Meanwhile, the brake Handle material has an Impact value of 0.81 J/cm², and an Impact value that is close to the standard brake Handle is found in 3% magnesium alloy with an Impact value of 0.98 J/cm². The percentage increase in Impact value due to the addition of magnesium was 93%. The hardness test results also show that the addition of magnesium by 3%, 4% and 5% increases the hardness value. 5% magnesium alloy has the highest hardness value of 111.84 Kg/mm², while the brake Handle material has a hardness value of 89.16 Kg/mm². A hardness value that is close to the standard brake Handle is found in 3% magnesium alloy with a hardness value of 93.83 Kg/mm². The percentage increase in hardness value due to the addition of magnesium is 40%.